Metode Pendidikan Akhlak untuk Sekolah Islam Perspektif Ibnu Abi al-Dunya dalam Kitab MakÄrimul AkhlÄq - Umar Bin Makka Lanye; M. Amirullah; Aswar, Aswar; Muhammad Ammar Naufal (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The crisis of moral education is one of the causes of the decline of today's people. A solution is needed in the form of the implementation of the moral education methods in the Islamic schools in developing civilization and restoring the glory of the people. This study aims to determine the moral education methods in the Islamic schools and its relevance based on the perspective of Ibnu Abi al-Dunya in the book of MakÄrimul AkhlÄq. The study used a qualitative research method with library research approach. Data analysis techniques used content analysis, descriptive, and inductive. The results showed that the methods of moral education from the perspective of Ibnu Abi al-Dunya included: qudwah, targÄ«b and tasywÄ«q methods, tarhÄ«b, at-ta'awwud, naá¹£Ä«á¸¥ah, and á¸¥iwÄr. The findings should be a concern for the educational process in the Islamic schools so that it can be implemented optimally and contribute in presenting reference materials to moral education methods that may be used in the Islamic schools.